The Grownup [compact disc, unabridged] - Flynn, Gillian, 1971- (Random House Audio ; Books on Tape, 2015)
When a charlatan "psychic" visits her Victorian home to find the source of her terror and grief, Susan, the psychic, and her teenage stepson are soon forced to confront the truth about ghosts.